Striving ascetics or vengeful martyrs? Militant pietism and death-related practices among Jahriyya Muslims of Northwest China - Previato, Tommaso (Journal of Contemporary East Asia Studies, 2025)
This paper draws on emic sources from the post-Mao Islamic revival (early 1980s to mid-2010s) to examine the remembrance of the dead in Jahriyya Sufism—a Chinese sectarian offshoot of the Yemeni Naqshbandi tradition whose shaykhs were executed in the wake of the 18th and 19th century rebellions against the Qing dynasty (1644–1912). It delves into the practice of memorializing martyrs in light of broader trends in classical and modern Sufism, with particular attention paid to self-purification (Ar. tazkiyah al-nafs) and other ascetic ideas that inform such a practice. The paper will address two core questions: Can the contemplation of death provide a pathway to moral edification? In what ways does the memory of martyrs affect the living practitioners? Anecdotal and documentary evidence of Jahriyya Muslims (i) showing devotion to their shaykhs in acts of extreme piety, or (ii) attending shrine pilgrimages (ziyārah, lit. “visit”) on the shaykhs’ death anniversaries will form the basis for a discussion on how memorial celebrations aid the practitioners’ quest for and experience of fanāʾ fi-l-Allah (“self-annihilation in God”).
CRIS-Team Scopus Importer:2025-05-09
Keywords: fanāʾ fi-l-Allah; Jahriyya; martyrdom; self-purification; shrine visitation